Metastatic gestational trophoblastic neoplasm presenting as spontaneous renal and cerebral hemorrhage with low titer of HCG: A case report of an unusual case - Moon, Hee Hyoun; Kim, Seok Mo; Moon, Jong Ho; Kang, Woo Dae; Choi, Ho Sun (Korean journal of obstetrics & gynecology, 2012)
Gestational trophoblastic neoplasm includes tumor spectrum of four entities: hydatidiform mole (complete and partial), invasive mole, choriocarcinoma and placental site trophoblastic tumor. The hydatidiform mole is usually benign, but it is regarded as a pre-malignant disease. The other three conditions are malignant and are termed gestational trophoblastic tumor. Although most molar pregnancies behave in a benign fashion, metastatic tumors develop after complete molar pregnancy in 4% of patients. However, even when the disease is spread to many distal organs, it is highly curable with chemotherapy in most cases. We recently encountered an unusual case of metastatic gestational trophoblastic neoplasm following complete mole, presenting as spontaneous renal and cerebral hemorrhage with a fatal course. KCI Citation Count: 0